The Utilization of Local Wisdom-based Interactive Digital Module to Improve Students’ Critical Thinking Skills - Syahfitri, Jayanti (International Journal of STEM Education for Sustainability, 2024)
Local wisdom-based interactive digital module is an alternative teaching material developed to provide students with meaningful learning and experiences. This study aimed to investigate the effect of Local wisdom-based interactive digital module on students' critical thinking skills. This study applied a quasi-experimental non-equivalent control group design involving 74 students who were divided into two groups, namely the experimental group and the control group. Learning in the experimental class used local wisdom-based interactive digital module, while learning in the control class used conventional teaching materials such as publishers' printed books. The results of the prerequisite test analysis show that the data are normally distributed and homogeneous. Furthermore, the data were analyzed through an independent sample t-test, which explained that applying Local wisdom-based interactive digital module could significantly improve students' critical thinking skills for all indicators. Module with attractive display innovations equipped with pictures, videos, audiovisuals, and quizzes in presenting content and local wisdom can stimulate students' motivation, curiosity, and analytical and evaluation skills to train the use of students' critical thinking skills in learning.